Integrasi Nilai Catur Piwulang dalam Bimbingan Kelompok Teknik Sosiodrama untuk Mengembangkan Sikap Altruis Siswa SMA - Alivia Eka Arianti; IM Hambali; Diniy Hidayatur Rahman (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Students' social problems with peers are often caused by a lack of altruism, such as increased selfish behavior, lack of concern for others, and weakened solidarity between students. This can trigger social conflicts such as bullying, intolerance, and violence. The purpose of this research is to analyze the value of Catur Piwulang Sunan Drajat in group guidance services through sociodrama techniques as an effort to develop altruist attitudes of high school students. The method used in this research is literature study by reviewing books, journals, and other literature. Furthermore, related data were collected, recorded, and analyzed descriptively and qualitatively. The results of this study indicate that the value of Catur Piwulang is closely related to altruist attitudes. The integration of Catur Piwulang values in group guidance services through sociodrama techniques is able to develop students' altruist attitudes with others. Through the use of sociodrama techniques can also reflect these values through role simulation and direct interaction, thus facilitating the internalization of altruist attitudes.This research is expected to be a reference for counseling teachers or counselors in developing more effective group guidance programs according to student needs, and in line with the values of local wisdom of Indonesian culture such as Catur Piwulang. In addition, the results of this study can also contribute to strengthening local culture-based character education to support the formation of a young generation that is not only intelligent, but also has high moral integrity.